Effects of an acute stressor on fear and on the social reinstatement responses of domestic chicks to cagemates and strangers - Marin, Raul Hector (2001)
Genetic selection for appropriate levels of sociality (motivation to be with conspecifics) could benefit poultry welfare and performance. Runway tests that require chicks to traverse a corridor in order to reach other chicks in a goal box are commonly used to measure this behavioural trait. However, we need to determine if the chicks' responses in such tests are sensitive to certain experiential variables before we can recommend possible selection criteria for future breeding programmes. The present study focused on fear and on the identity of the stimulus birds. Broiler chicks either remained undisturbed or were exposed to an acute stressor (mechanical restraint) before their tonic immobility fear responses were measured 1 h later in Experiment 1. Exposure to the stressor significantly prolonged tonic immobility and, hence, presumably, underlying fear levels. In Experiment 2, the responses of stressed chicks and undisturbed controls were assessed when they were tested individually in a runway with a goal box containing either familiar or unfamiliar chicks of the same age. Our finding that stressed chicks emerged from the start box sooner and spent longer near the stimulus birds suggests that exposure to a frightening event increased social reinstatement motivation. Furthermore, social affiliation was more pronounced when the goal box contained familiar cagemates rather than strange chicks, regardless of prior treatment. This finding demonstrates that broiler chicks that were housed in groups of twelve can discriminate between familiar and unfamiliar conspecifics encountered in novel surroundings. Thus, sociality was positively associated with fearfulness and broilers clearly showed social discrimination in runway tests. These findings highlight the dangers of disregarding variables, such as fear and the capacity for social recognition in tests of social motivation. We strongly recommend that exposure to frightening events prior to test should be avoided and that the identity of the birds in the runway goal box should be standardized, i.e. either familiar or unfamiliar, and noted. © 2001 Elsevier Science B.V.